DETERMINING FACTORS OF GEN-Z VOTERS’ PREFERENCES IN REGIONAL ELECTIONS: A CASE STUDY OF THE 2024 ACEH TENGGARA REGENCY ELECTION - Fasrah Indah; Katimin Katimin; Syukri Syukri (UNIVERSITAS PAKUAN, 2025)
This study analyzed the factors influencing the political preferences of Generation Z (Gen-Z) voters in the 2024 Regent Election (Pilkada) of Southeast Aceh. Employing a qualitative approach through an intrinsic case study, the research explored the subjective experiences and socio-political dynamics of Gen-Z in shaping their political choices. Data were collected through in-depth interviews, participatory observation, and digital documentation involving 30 respondents selected through purposive sampling. The findings revealed that Gen-Z’s political preferences were shaped by issue-based rationality, candidate capability, and perceptions of personal branding and leadership integrity. Social media platforms—particularly TikTok, Instagram, and YouTube—emerged as the primary channels for political socialization, while local figures such as teachers and religious leaders (ustadz) continued to hold influence within limited social contexts. Challenges to participation included low levels of political literacy, the spread of misinformation, and limited internet access in rural areas. Nonetheless, Gen-Z demonstrated active, selective, and critical engagement with political messages. This study affirmed the relevance of rational choice theory and cognitive domains in explaining young voter behavior and recommended campaign strategies that were educational, value-based, and inclusive of digital generation voices.